Societal Determination of Professional Identity in Russian Society - Klimenko, Ludmila; Posukhova, Oxana (Opción, 2019)
The aim of the article is to study the integrative and disintegrative nature of professional identity under institutional changes in Russian society. The methodological base of the research involves concepts of societal effect and precarization. As a result, behavioral patterns are associated mostly with balance disadvantage of social risks, especially with the threat of downward social mobility. In conclusion, professional identity among Russian working class becomes diffuse, unstable, with reducing the impact of incentives providing its dynamism – mindset on professional activity, professional growth, acquisition of new skills and knowledge.